Effects of Drip System Uniformity and Irrigation Amount on Water and Salt Distributions in Soil Under Arid Conditions - Hong-jie GUAN; Jiu-sheng LI; Yan-feng LI (Journal of Integrative Agriculture, 2013)
The dynamics of water and salt in soil were monitored in the 2010 and 2011 growing seasons of cotton to evaluate the salinity risk of soil under drip irrigation in arid environments for different management practices of drip system uniformity and irrigation amount. In the experiments, three Christiansen uniformity coefficients (CU) of approximately 65, 80, and 95% (referred to as low, medium, and high uniformity, respectively) and three irrigation amounts of 50, 75, and 100% of full irrigation were used. The distribution of the soil water content and bulk electrical conductivity (ECb) was monitored continuously with approximately equally spaced frequency domain reflectometry (FDR) sensors located along a dripline. Gravimetric samples of soil were collected regularly to determine the distribution of soil salinity. A great fluctuation in CU of water content and ECb at 60 cm depth was observed for the low uniformity treatment during the irrigation season, while a relatively stable variation pattern was observed for the high uniformity treatment. The ECb CU was substantially lower than the water content CU and its value was greatly related to the water content CU and the initial ECb CU. The spatial variation of seasonal mean soil water content and seasonal mean soil bulk electrical conductivity showed a high dependence on the variation pattern of emitter discharge rate along a dripline for the low and medium uniformity treatments. A greater irrigation amount produced a significantly lower soil salinity at the end of the irrigation season, while the influence of the system uniformity on the soil salinity was insignificant at a probability level of 0.1. In arid regions, the determination of the target drip irrigation system uniformity should consider the potential salinity risk of soil caused by nonuniform water application as the influence of the system uniformity on the distribution of the soil salinity was progressively strengthened during the growing season of crop.